DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Nazirova Diyoraxon; Jalolova Muqaddas (TADQIQOTLAR, 2025)
Abstract This thesis examines the challenges associated with teaching foreign languages to young learners, highlighting key factors that influence language acquisition in early childhood education. It identifies cognitive development as a primary challenge, noting that young children often struggle with abstract concepts and have limited attention spans, necessitating interactive and age-appropriate teaching methods. The study also addresses  the  importance  of  motivation  and  interest  in  the  learning  process, emphasizing the need for engaging activities that resonate with children's experiences.